The Teacher’s Role in Students’ Math Anxiety - Birchall, Rebecca S. (Learning to Teach Language Arts, Mathematics, Science, and Social Studies Through Research and Practice, 2018)
It is a well-known fact that math can become a disliked subject once students begin to approach more complex topics. Students associate anxiety with the subject and their confidence decreases as a result. This unpleasant emotional response prevents students from successfully learning math. Educators need to dismiss this apprehension towards mathematics. Each teacher has their own way of looking at mathematics. The question is, how do we accomplish this anxiety reduction when all teachers perceive math differently? Teachers’ attitudes towards math can also have an enormous effect on how their students will perceive math. How much do educators’ perceptions of their own subject positively or negatively affect mathematical anxiety?